ANALISIS NILAI-NILAI PENDIDIKAN MORAL PADA ANIMASI “IBRA BERKISAH” DAN RELEVANSINYA DENGAN MATERI AKIDAH AKHLAK KELAS VIII MTS - Nasikhah, Ulfatun; Mufid, Mufid (Raudhah - Proud To Be Professional, 2025)
This study aims to analyze the values ​​of moral education contained in the animated series "Ibra Bercerita" and to spread its relevance to the Aqidah Akhlak material taught in class VIII of Madrasah Tsanawiyah (MTs). The research method used is a literature review method with a content analysis approach. Data were collected through observations of selected episodes of the animated series and analyzed to identify the moral values ​​contained therein, such as ikhtiar, tawakal, terimakasih, sabar, qanaah, husnudzon, tawadhu, tasamuh, and taawun. The results of the study indicate that the animation "Ibra Bercerita" contains various moral education values ​​that are in accordance with the Aqidah Akhlak material of class VIII of Madrasah Tsanawiyah. The implementation of these values ​​in classroom learning can enrich students' learning experiences and support the achievement of moral education goals. This study recommends the use of animation media as an effective learning tool to teach moral values ​​to students.